2024
DOI: 10.1021/acsphotonics.3c00973
|View full text |Cite
|
Sign up to set email alerts
|

On-Demand Generation of Indistinguishable Photons in the Telecom C-Band Using Quantum Dot Devices

Daniel A. Vajner,
Paweł Holewa,
Emilia Zięba-Ostój
et al.

Abstract: Semiconductor quantum dots (QDs) enable the generation of single and entangled photons, which are useful for various applications in photonic quantum technologies. Specifically for quantum communication via fiber-optical networks, operation in the telecom C-band centered around 1550 nm is ideal. The direct generation of QD-photons in this spectral range with high quantumoptical quality, however, remained challenging. Here, we demonstrate the coherent on-demand generation of indistinguishable photons in the tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…A telecom single-photon source operating around 1,550 nm (C-band) is essential for fiber-based quantum communication networks to minimize transmission loss in the silica fiber. Various approaches have been explored to realize single-photon sources within this spectral window, including spontaneous parametric down-conversion, , as well as materials such as carbon nanotubes, and semiconductor quantum dots. , Among these methods, single photon sources based on semiconductor quantum dots are considered most promising due to their high brightness, , high purity, , and indistinguishability. For example, InAs/InP quantum dots emit single photons in the telecom C-band spectrum, , which have been extracted utilizing various device structures, such as mesa structures, planar cavities, nanowires, and photonic crystal cavities . However, more efficient coupling to the optical fiber is needed to collect the telecom C-band single photon emission with high efficiency for long-distance quantum networks.…”
Section: Introductionmentioning
confidence: 99%
“…A telecom single-photon source operating around 1,550 nm (C-band) is essential for fiber-based quantum communication networks to minimize transmission loss in the silica fiber. Various approaches have been explored to realize single-photon sources within this spectral window, including spontaneous parametric down-conversion, , as well as materials such as carbon nanotubes, and semiconductor quantum dots. , Among these methods, single photon sources based on semiconductor quantum dots are considered most promising due to their high brightness, , high purity, , and indistinguishability. For example, InAs/InP quantum dots emit single photons in the telecom C-band spectrum, , which have been extracted utilizing various device structures, such as mesa structures, planar cavities, nanowires, and photonic crystal cavities . However, more efficient coupling to the optical fiber is needed to collect the telecom C-band single photon emission with high efficiency for long-distance quantum networks.…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the QD excitations tend to be dimmer due to their longer lifetime, requiring longer exposure times. For neutral excitons generated by above-band excitations, previous studies reported lifetimes of approximately 1.29 ns for InAs QDs grown on a metamorphic buffer (MMB) [27] and 1.32 ns for InAs/InP QDs [28], both emitting in the Cband. In comparison, the decay time decreases to about 200 ps for GaAs QDs in nanoholes emitting around 795 nm [29,30] and about 800 ps for InGaAs/GaAs emitting between 900 and 950 nm [18].…”
Section: Introductionmentioning
confidence: 99%
“…As the (single-peak) FPI line widths of the different excitation schemes are similar, this indicates that spectral diffusion (and line jumps) takes place on a shorter time scale for the SUPER than for LA. However, this degree of indistinguishability represents not only an improvement compared to the SUPER scheme but also previously reported results on In(Ga)As QDs in the telecom C-band , and a performance similar to the currently highest reported value across all telecom C-band QD sources …”
mentioning
confidence: 99%
“…Apart from the single-photon nature, the indistinguishability and line width of emitted photons become key figures of merit for interference-based applications such as quantum teleportation , and quantum repeater protocols , that are envisioned to play a pivotal role in long-distance quantum communication . However, with respect to these properties, QDs with emission in the telecom C-band have yet to demonstrate values comparable to those of their well-investigated near-infrared (NIR) counterparts. …”
mentioning
confidence: 99%